Use of a CPD Plan Template with SMART Goals as Part of a Diabetes Pharmacotherapy Module - Byrdena DeeAnn Dugan; P.J. Hughes; Sarah Wright (University of Minnesota Libraries Publishing, 2020)
Objective: To evaluate the effectiveness of a Continuing Professional Development (CPD) plan template used in Fall of 2017 on quality of SMART goal development and student quiz scores. Innovation: The gap in time from when pharmacology is taught and when it is applied has contributed to poor student retention and performance in the diabetes pharmacotherapy course. To address this gap, the diabetes pharmacotherapy learning sequence was redesigned and included a self-assessment (pre-test), and the completion of a "CPD plan template", which involved writing 1-3 SMART goals for each question missed on the pre-test. Following sequence completion, students took an identical post-quiz. Pre- and post- quiz scores were compared. Quality of CPD plan SMART goals was evaluated. Key Findings: The CPD plan template was completed by 98% of students.  The majority, 62.5% of students, wrote SMART goals at the intermediate or good level, while 37.5% were evaluated as needs improvement. The average pre-quiz score was 7.4 points and average post-quiz score was 17.1 points with an average improvement of 9.8 points (p<0.0001). There was a statistically significant improvement for top 25% post-quiz scoring students who wrote "good" SMART goals compared to those who wrote goals needing improvement (p= 0.002). For students scoring in the lowest 25%, students with goals needing improvement scored higher than those with intermediate quality goals (p< 0.04). Next Steps: It may be beneficial to introduce CPD to students sooner, as well as teach students more intentionally how to create and use SMART goals to improve learning. Finally, instructor follow up with students regarding use of their plan during a learning sequence may have additional benefit.   Article Type: Note